Magnetron deposition of chromium nitride coatings using a hot chromium target: Influence of magnetron power on the deposition rate and elemental composition; Surface and Coatings Technology; Vol. 433 - Grudinin V. A. Vladislav Alekseevich; Bleykher (Bleicher) G. A. Galina Alekseevna; Sidelev D. V. Dmitry Vladimirovich; Yuriev Yu. N. Yuri Nikolaevich; Lomygin A. D. Anton Dmitrievich (2022, 2022)
Title screen